Continuum structure in strong electromagnetic fields - O'Connor, Michael (Not Specified, 2024)
[Pages missing ] In this chapter, the Dirac equation for spherically symmetric potentials is closely examined. Analytical solutions are found for a square well potential, the properties of which will be used later when the equation is solved for arbitrary potentials using numerical methods. The starting point is the Dirac equation for stationary states. For convenience, the units are chosen such that h=c=l. However, in explicit calculations, these constants are re-introduced using the prescription hc=197 Mev fm. When the coupling constant a is used, its value is taken as 1/137.